Effect of Climate Change on Rainfall in the Upper Basin of Chicamocha River in the Period of 1980-2012. - Garavito Rincón, Laura Natalia; Caro Camargo, Carlos Andrés (TECCIENCIA, 2018)
Indications suggest that anthropic activities have altered the atmospheric composition, causing alterations in elements generating extreme weather events and contributing to what we know today as global warming, through global and local changes in the rain regime and other climatic variables that interact in the hydrological cycle, causing extreme events with greater frequency. It is necessary to know the trends and extreme events of rains in order to have a basis for the adaptation and prevention of natural disasters caused by these macroclimatic phenomena. Through non-parametric tests, we found an increasing trend in rainfall between 5% to 20% average, in comparison with the behavior in the period of 1980 to 1990. Similarly, the influence of the macroclimatic variables in rainfall behavior is null.